Does Relationship Quality Affect Customer Loyalty of Malaysian National Carmakers: Alternative Attractiveness as Moderator - Zainil Hanim Saidin; Wan Afezah Wan Abdul Rahman; Beni Widarman Yus Kelana; Rawiyah Abd Hamid (International Journal of Supply Chain Management, 2018)
This paper aims to explore how the intangible element of relationship quality influences the level of customer loyalty towards Malaysian national carmakers in the competitive business of automotive after-sales service. After-sales service is a good platform to retain the customers for a longer term of relationship which creates sustainable business opportunities. The repeated service encounter during the given free warranty period has developed a continuous customer-service provider relationship. Most importantly, the sales of a vehicle have offered existing customers after-sales service business. However, the attractive offers from ordinary workshops have encouraged the existing customers to choose ordinary workshops after the vehicle warranty has expired and the existing relationship with the current service provider is terminated. The loss of existing customers has denied the opportunity for the national carmakers to take advantage of recommendations, referrals, good publicity, and positive word-of-mouth that contribute to a higher level of customer loyalty. Using PLS-SEM as the method of data analysis, this study empirically tested the influence of relationship quality as the independent variable towards customer loyalty while competition variable of alternative attractiveness was tested as a moderator. The data were collected from 312 respondents through the technique of intercept survey and the respondents were chosen based on systematic sampling. The findings revealed that relationship quality was positively related to customer loyalty. However, alternative attractiveness was not significant as a moderator in the relationship between relationship quality and customer loyalty. Based on the results, this study empirically proved that high quality of relationship gives more impact towards customer loyalty compared to other competitors offers. This study benefited the Malaysian national carmakers as it provides empirical evidence on the importance of high-quality customer-service provider relationship which might assist them to develop a unique marketing strategy to retain the existing customers and generates more loyal customers.